Insight into fermentable sugar recovery process from sugarcane bagasse: in silico elucidation of enzymatic hydrolysis and techno-economic assessment. Issue 1 (31st December 2022) - Anand, Shreya; Muthu Kumar, Sampath; Mukherjee, Koel; Padmanabhan, Padmini
Abstract : A technological scheme was developed to produce 2G fermentable sugar from sugarcane bagasse and was assessed for the process feasibility. This paper describes recovery of fermentable sugar, characterization of pretreated hydrolysed bagasse, in-silico elucidation of enzymatic hydrolysis and techno-economic analysis of the recovery of sugar from bagasse. The in-silico approach included characterization of both the enzymes, estimation of physiochemical and functional properties through ProtParam. Secondary structures of enzymes were represented using SOPMA. Modelling of enzymes was done using MODELLER 9.24. The developed model was validated through PROCHECK and was evaluated using Verify3D. The active sites of both the enzymes were predicted using 3D LigandSite – Ligand binding site prediction server and molecular docking of the predicted Models were performed using Swiss Dock. The techno-economic analysis showed 0.516 kg (2G fermentable sugar)/kg bagasse). GRAPHICAL ABSTRACT: UF0001